Perspectives on school violence: novice teachers' experiences in Thai urban secondary schools - Chobphon, Peson (Frontiers in Education, 2025)
Prior research has called for schoolteachers to recognize that they can have a significant impact on school violence prevention. Additionally, authorities should realize the importance of providing knowledge and creating policies and activities that enable teachers to utilize their full potential to prevent violence in schools. This phenomenological study examined the perspective of eight new schoolteachers from eight different public schools in Bangkok regarding school violence. They were individually interviewed and the collected data were analyzed thematically. This study revealed their understandings of school violence and the way their schools dealt with violent incidents. Factors that hindered their decisions to intervene were a lack of knowledge of school violence or support from school authorities, a lack of empathy, a wider hierarchical structure, a lack of self-efficacy, and misinformed perceptions of the seriousness of verbal bullying and social exclusion. To counter Thai societal normalization of bullying, the text argues for the implementation of comprehensive training, policies, and counselling services that prioritize positive reinforcement to de-normalize abuse. Aligning with Bandura's findings on the link between teacher perceptions and interventions, the study emphasizes that stakeholders must equip new teachers with theoretical knowledge and relationship-building skills to enhance their self-efficacy in preventing violence.